Chinese Stroke Association guidelines for clinical management of cerebrovascular disorders: executive summary and 2019 update of clinical management of ischaemic cerebrovascular diseases. Issue 2 (18th June 2020) - Liu, Liping; Chen, Weiqi; Zhou, Hongyu; Duan, Wanying; Li, Shujuan; Huo, Xiaochuan; Xu, Weihai; Huang, Li'an; Zheng, Huaguang; Liu, Jingyi; Liu, Hui; Wei, Yufei; et al.
Abstract : Aim: Stroke is the leading cause of disability and death in China. Ischaemic stroke accounts for about 60%–80% of all strokes. It is of considerable significance to carry out multidimensional management of ischaemic cerebrovascular diseases. This evidence-based guideline aims to provide the latest detailed and comprehensive recommendations on the diagnosis, treatment and secondary prevention of ischaemic cerebrovascular diseases. Methods: We had performed comprehensive searches of MEDLINE (via PubMed) (before 30 June 2019), and integrated the relevant information into charts and distributed to the writing group. Writing group members discussed and determined the recommendations through teleconference. We used the level of evidence grading algorithm of Chinese Stroke Association to grade each recommendation. The draft was reviewed by the Guideline Writing Committee of Chinese Stroke Association Stroke and finalised. This guideline is fully updated every 3 years. Results: This evidence-based guideline is based on the treatment, care and prevention of ischaemic cerebrovascular diseases, which emphasises on pathogenesis evaluation, intravenous thrombolysis, endovascular therapy, antiplatelet therapy, prevention and treatment of complications, and risk factor management. Conclusions: This updated guideline presents a framework for the management of ischaemic cerebrovascular diseases. Timely first-aid measures, professional care in the acute stage, and proactive secondary prevention will be helpful to patients.